Characterization of creamy sauce made with cryoconcentrated soymilk (Research, Society and Development, 2020)
Creamy sauces are consumed worldwide and can be formulated using different ingredients, obtaining products with some specific characteristics. The objective of this work was to evaluate the physical-chemical characteristics and sensory acceptance and the hygienic-sanitary conditions of the creamy sauce made with cryoconcentrated soymilk. The cryoconcentrated soymilk, salt, sugar, citric acid, xanthan gum, phosphoric acid and potassium sorbate were homogenized; the soy oil was added slowly with stirring to form the emulsion. The creamy sauce, made without the addition of eggs, was evaluated for its physical-chemical characteristics, hygienic-sanitary conditions and sensory acceptance. The creamy sauce showed good nutritional characteristics with a higher protein content, lower lipid content and cholesterol free, comparing with commercial mayonnaise. The pH and acidity of the creamy sauce were low. The evaluation of the hygienic-sanitary conditions of the creamy sauce indicated that the product is safe for consumption and meet the specifications of legislation. The microstructure of the creamy sauce was dispersed with highly packaged oil droplets of different sizes and polydispersed. The color of the sauce was light and with a tendency towards green and yellow. Acceptance was satisfactory with 70% approval and the most accepted attributes were color and texture. The purchase intention was over 90%. The formulation of the creamy sauce using the cryoconcentrated soymilk and different ingredients can be modified to improve some characteristics and validity of the product.